2009
DOI: 10.1055/s-0029-1185865
|View full text |Cite
|
Sign up to set email alerts
|

Two New Cytotoxic Triterpene Glycosides from the Sea CucumberHolothuria scabra

Abstract: Two new triterpene glycosides, scabraside A (1) and B (2), and a structurally known compound (3), were isolated from the sea cucumber Holothuria scabra (Holothuriidae) collected from the South China Sea. Structure of these compounds was elucidated by spectroscopic and chemical methods. The glycosides 1 and 2 exhibit the same common structural features, i. e., the presence of 12- and 17-hydroxy groups in the holostane-type triterpene aglycone with a 9(11)-ene bond, but are different in the side chains of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 10 publications
2
36
0
Order By: Relevance
“…It is observed that Hep2 cell line was more sensitive to the active extracts than Vero cells. This is in agreement with Han et al (2009) who reported that different cell lines exhibit different responses to the cytotoxic compounds of seacucumbers. The morphological changes and changes in membrane permeability could be easily inferred from the images observed in our experiment through the inverted microscope among the cell lines of Vero and Hep2.…”
Section: Discussionsupporting
confidence: 94%
“…It is observed that Hep2 cell line was more sensitive to the active extracts than Vero cells. This is in agreement with Han et al (2009) who reported that different cell lines exhibit different responses to the cytotoxic compounds of seacucumbers. The morphological changes and changes in membrane permeability could be easily inferred from the images observed in our experiment through the inverted microscope among the cell lines of Vero and Hep2.…”
Section: Discussionsupporting
confidence: 94%
“…The MALDI analysis revealed that the ion with m/z 1243.5 was the prominent peak in the spectrum, which corresponded to Holothurin A, which was found in several species of sea cucumbers [6,29,50,58,61,64,89,95,96,97]. The MALDI data were confirmed by ESI-MS.…”
Section: Resultsmentioning
confidence: 75%
“…They are reported primarily as typical metabolites of terrestrial plants [25]. A few marine species belonging to the phylum Echinodermata [26] namely holothuroids (sea cucumbers) [7,10,13,27,28,29,30,31,32,33] and asteroids, and sponges from the phylum Porifera [13,34,35] produce saponins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen pure triterpene glycosides ( 1 – 13 , Figure 1) were isolated from H. scabra Jaeger ( 1 – 9 ) and Cucumaria frondosa Gunnerus ( 10 – 13 ) (Holothuriidae) as previously described [22,23,24,25,26]. Each of the isolates was subjected to detailed spectroscopic analysis (IR, EI-MS, ESI-MS, HRESI-MS, 1 H-NMR, 13 C-NMR, 1 H- 1 H COSY, DQCOSY, TOCSY, HMQC, HMBC and NOESY) to identify their chemical structures.…”
Section: Methodsmentioning
confidence: 99%